Intraseasonal variability of the Indonesian throughflow associated with the Madden-Julian Oscillation. (November 2021) - Nieva Tamasiunas, Mariana C.; Shinoda, Toshiaki; Susanto, R. Dwi; Zamudio, Luis; Metzger, E. Joseph
Abstract: Intraseasonal variability (20–90 days) of the Indonesian Throughflow (ITF), which is primarily forced by the Madden-Julian Oscillation (MJO), is investigated using a high-resolution global ocean reanalysis and satellite altimeter data. Previous studies show that during the MJO active phase, downwelling Kelvin waves generated in the central equatorial Indian Ocean propagate along the coast of Sumatra and Java islands, affecting the ITF transport at exit passages in the Indonesian Seas and Makassar Strait. However, the intraseasonal variation of the ITF transport through these straits over the MJO life cycle, especially during the suppressed phase, has not been quantified. To quantify the ITF transport associated with the MJO, composites of ITF transport through major straits in the Indonesian Seas are constructed using a 0.08° global HYbrid Coordinate Ocean Model (HYCOM) reanalysis. A prominent reduction of ITF transport through major straits is found during the MJO active phase, and a transport enhancement comparable to the reduction is evident during the suppressed phase. As a result, the net effect of the MJO on the mean ITF transport is very small due to the cancellation of the enhancement and reduction. The magnitude of the MJO-associated ITF transport variation through all ITF exit passages is about 6 Sv, which is about 50% of the total transport. While the propagation of coastal Kelvin waves during the MJO active phase and their impact on ITF transport is clearly evident in the composite, such Kelvin wave influence on ITF transport is not clearly detected during the suppressed phase. This suggests that anomalous winds over the Maritime Continent (MC) area are mostly responsible for the ITF variation during the suppressed phase in many MJO events. Yet, during some MJO events, remotely-forced upwelling Kelvin waves and their significant impact on the ITF transport are evident during the MJO suppressed phase.